Indirect partner choice through manipulation of male behaviour by female fowl, Gallus gallus domesticus. - Pizzari, T (2001)
The direct and indirect consequences of female copulatory behaviour for copulation success have seldom been quantified. In feral fowl, most copulations were forced by males and copulation success was determined by two factors. First, female differential resistance and solicitation directly affected copulation success and were displayed non-randomly with respect to male social status. Second, another female copulatory behaviour, the distress call, had an indirect effect on both copulation success and the quality of copulation partners. Distress calls triggered male attention to a copulation, which increased the probability of higher-ranking males than the copulating male disrupting the copulation and inseminating the calling female. Females preferentially uttered distress calls when mounted by low-ranking males. Both copulation resistance and distress calling influenced copulation success, but only distress calling increased the probability of copulation disruption by other males. Consistent with the effect of direct selection, differential distress calling indirectly biased copulation success in favour of dominant males. Female fowl may thus ameliorate the effect of male sexual coercion by manipulating male behaviour.